Clinical Phenotype and Inheritance in Patients With C9ORF72 Hexanucleotide Repeat Expansion: Results From a Large French Cohort - Esselin, Florence; Mouzat, Kevin; Polge, Anne; Juntas-Morales, Raul; Pageot, Nicolas; De la Cruz, Elisa; Bernard, Emilien; Lagrange, Emmeline; Danel, Véronique; Alphandery, Sébastien; Labar, Laura; Nogué, Erika; et al. (Frontiers in Neuroscience, 2020)
Background In familial amyotrophic lateral sclerosis (ALS) cases, the presence of an abnormal C9ORF72 repeat expansion (C9RE) is the most frequent genetic cause identified. Various clinical phenotypes have been described in relation to the presence of C9RE, including psychiatric disorders or Huntington-like symptoms. In a subset of sporadic ALS, C9RE has also been described. In the present study, all index cases with ALS and C9RE identified in our center and their clinical profile, as well as neurological and psychiatric characteristics of identified family members, were described. Clinical characteristics of ALS patients were compared to 999 patients with sporadic ALS (SALS) from our database. Results From the 70 index cases with ALS identified, a total of 200 individuals were studied, 118 with ALS, 32 with fronto-temporal lobe degeneration (FTD), 37 with ALS/FTD, and 13 with psychiatric disorders. A familial history was present in 57 of the index cases (81%). In ALS and ALS/FTD cases with C9RE, the age of onset (AoO) was earlier than that in SALS cases, p < 0.0001 and p = 0.008, respectively. Sporadic cases with C9REALS (n = 13) had an earlier AoO compared to familial C9REALS ones, p < 0.0001. Within families, there was an earlier AoO in index cases and their siblings compared to their parental generation (p < 0.01). There was also a significant intrafamilial correlation for bulbar onset of ALS. The parental generation had significant female predominance compared to index cases and their siblings (sex ratio 0.47 vs. 1.4, p = 0.004), and this predominance was also present when considering parent–child pairs. In the group with psychiatric disorders, suicide was prominent (n = 9) and mean age was 54 years. Conclusion Although our sample size is rather limited, the earlier AoO in index cases and their siblings compared to the parental generation may suggest an anticipation. Reasons for predominance of female transmission are unclear, but the hypothesis that gender influences transmission of the genetic trait or C9RE size variation may be taken into account. Intrafamilial correlation suggests that genetic aspects underlie the occurrence of bulbar onset in ALS patients. Studies on larger samples are warranted to confirm those results.